(untitled) (Journal of Global Humanities and Social Sciences, 2025)
This paper discusses the strategic orientation of corporate culture in enterprise management, understands corporate culture, clarifies its strategic orientation, and discusses and describes the specific measures to play its strategic role. Hope to provide reference for the development of related work to ensure the stability and health of enterprise development.